Comparative Study of Biopolymer Flooding: A Core Flooding and Numerical Reservoir Simulator Validation Analysis - Akinleye Sowunmi; Vincent E. Efeovbokhan; Oyinkepreye D. Orodu; Oluwasanmi Olabode; Alma Oputa (Modelling and Simulation in Engineering)
Polymers increase the macroscopic efficiency of the flooding process and increase crude oil recovery. The viscosity of 3 polymers xanthan, guar, and Arabic gums is measured in the lab and experimented with as EOR options. Xanthan and guar gum polymers are measured in weight percentages of 0.1, 0.2, 0.2, 0.4, 0.5, and 1, while gum Arabic is measured in 0.4, 0.5, 1, 5, 10, and 15 weight percentages. The viscosity experiments showed that gum Arabic had the lowest viscosity at 15% wt. Xanthan gum and guar gum had significantly higher viscosities than gum Arabic at corresponding weight percentages. At the same weight of 0.5%, xanthan, guar, and Arabic gums recorded a 63%, 53%, and 46% oil recovery, respectively. Due to the limitations surrounding core flooding experiments such as human error, equipment failure, and measurement of oil recoveries, it is necessary to validate the results obtained with other methods such as reservoir simulation. A reservoir model is built (using Eclipse) and incorporated with polymer and viscosity functions measured in the lab to validate results from the core flooding experiments. Peak oil recovery of 9.96%, 9.95%, and 9.90% was recorded for xanthan, guar, and Arabic gum, respectively, at a weight percentage of 0.5% weight. Also, increasing the wt% of injected polymers increases oil recovery. Results also indicate that the trend of oil recoveries during core flooding follows that observed during reservoir simulation and oil production increased as percentage weight increased for all the polymer cases considered.